2011
DOI: 10.1103/physrevb.84.195202
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular bridges and carrier traps in defective C60crystals

Abstract: Native point defects affect the physical properties of electronic materials and related devices. Here we employ first-principles calculations to address the role of vacancies and self-interstitials in the widely used organic semiconductor C 60 . We find that several stable defect configurations introduce levels in the energy-band gap of C 60 fullerite crystals, creating traps for charge carriers. We also find that while certain metastable point-defect structures bear finite magnetic moments, the lowest-energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…The structures of the fullerene before and after the migration event shown in Figure S2 of Supplementary Information are indicated. correspond to the barriers of hopping of the same sp atom in the odd C61 fullerene between the 5-6 and 6-6 positions 73 . Such a hopping, which is another possible way to switch the position of the sp atom relative to the sp 2 structure of the corresponding even fullerene (in addition to the sp-defect migration), has not been observed in our MD simulations.…”
Section: Iiib Dft Study Of Sp-defect Migration Energeticsmentioning
confidence: 99%
“…The structures of the fullerene before and after the migration event shown in Figure S2 of Supplementary Information are indicated. correspond to the barriers of hopping of the same sp atom in the odd C61 fullerene between the 5-6 and 6-6 positions 73 . Such a hopping, which is another possible way to switch the position of the sp atom relative to the sp 2 structure of the corresponding even fullerene (in addition to the sp-defect migration), has not been observed in our MD simulations.…”
Section: Iiib Dft Study Of Sp-defect Migration Energeticsmentioning
confidence: 99%
“…However, this is based on assumptions which, it has been seen here, are not necessarily correct. Moreover, although corrections to GGAs have a significant effect on the weak interatomic forces responsible for the interlayer binding of graphite, this is small in comparison with the strength of bonds between atoms in defects and their host [98,99]. An equally practical approach to this problem is to accept that the LDA provides a better description of interlayer binding in graphite than GGAs.…”
Section: Interlayer Bondingmentioning
confidence: 99%
“…32 Later density functional theory (DFT) calculations identified the [6,5] bridge as the most stable favored by 0.3 eV. 33 Our own DFT calculations with results summarized in Table 1S in the Supporting Information agree with this latter stability order; we found that the [6,5] bond is slightly preferred to the [6,6] bond with a bond energy D e (dissociation energy of the carbon adatom) of 2.82 eV on the [6,5] bond. This compares with 3.52 eV for the cation and 3.39 eV for the anion.…”
mentioning
confidence: 99%